PENGARUH RETURN ON EQUITY (ROE) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT GAJAH TUNGGAL TBK PERIODE TAHUN 2011-2020 - Hendri Gunawan; Henni Marlinah; Devi Putri Isnaeni (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of Return On Equity (ROE) and Debt To Equity Ratio (DER) partially and simultaneously on the stock price of PT Gajah Tunggal Tbk. The independent variables used in this research are Return On Equity (ROE) and Debt To Equity Ratio (DER). While the dependent variable used in this study is the stock price. The population in this study includes all the financial statements of PT Gajah Tunggal Tbk listed on the Indonesia Stock Exchange (IDX), the sample of this research data is the company's financial statements in the form of the Balance Sheet and Profit and Loss of PT Gajah Tunggal Tbk for the period 2011-2020. The method used in this study this is multiple linear regression analysis. Hypothesis testing was carried out using statistical tests, namely the T test (partial) and the F test (simultaneous). The data source for this research is the official website of PT Gajah Tunggal Tbk. Furthermore, the data collection method used in this study is a type of quantitative data. The results of this study indicate that partially Return On Equity (ROE) and Debt To Equity Ratio (DER) have a negative and insignificant effect on stock prices at PT Gajah Tunggal Tbk. Simultaneously, Return On Equity (ROE) and Debt To Equity Ratio (DER) have a negative and insignificant effect on the stock price of PT Gajah Tunggal Tbk.